Belief and Boundary Controls on Employee and Bank Performance - Riski Hernando; Eko Prasetyo; Primadi Prasetio; Rezi Abdurrahman; Ivan Leonardo (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2026)
This study examines the effects of belief and boundary control systems, two dimensions of Simons’ levers of control, on employee and banking performance in a regional development bank. Data were collected from 60 employees of Bank Pembangunan Daerah (BPD) Jambi and analyzed using SEM–PLS. The findings indicate that belief controls enhance employee performance but have no direct effect on banking performance. Conversely, boundary controls improve banking performance without significantly influencing employee performance. Employee performance positively affects banking performance, suggesting a mediating mechanism. This study extends the management control literature by demonstrating the complementary roles of belief and boundary controls beyond the dominant focus on diagnostic and interactive systems. The results highlight the importance of balancing motivational and compliance-based controls to strengthen both individual and organizational performance in emerging economy banking institutions.